Study of clinical and dermoscopic features in nails of papulosquamous disorders and their correlation with disease severity: A cross-sectional study - Anita Subudhi; Swapna Jena; Prasenjeet Mohanty; Dinesh R Panda (Wolters Kluwer Medknow Publications, 2022)
Background: As face is the index of the mind, so is the nail the index to health, as the nail is capable of mounting only a limited number of reaction patterns to the large number of disorders affecting it. Dermoscopy is thus a valuable aid not only in enhancing visible nail features but also in revealing cryptic features of diagnostic value. Aims: To study the clinical and dermoscopic features in nails of papulosquamous disorders and correlate it with disease severity. Methods and Material: This was a cross-sectional study with convenient sampling. After obtaining ethical clearance, according to inclusion and exclusion criteria, papulosquamous disorders were enrolled in the study. Finger nails and toe nails were numbered 1-10. Detailed clinical examination was done. Wet and dry dermoscopic examination was made in both polarised and non-polarised mode using ultrasound (USG) gel. Psoriasis area and severity index (PASI) and body surface area (BSA) were compared with nail changes. Statistical analysis of data was performed using the Statistical Package for the Social Sciences (SPSS) version 26. Results: Out of 203 patients, 117 were male. Psoriasis was the most common disease (55.6%). A total of 65.51% of patients had nail changes. Pitting was the most common finding in psoriasis, both dermoscopically and clinically. Splinter haemorrhage, oil drop, dilated capillaries, and pseudofibre sign were detected better on dermoscopy (P < 0.05). Positive correlation was found between PASI and nail psoriasis severity index (NAPSI). A strong correlation was also found between clinical (cNAPSI) and dermoscopic (dNAPSI). Thinning was the most common in lichen planus. No relation between BSA and nail changes was observed. Conclusions: Dermoscopy is thus a valuable aid not only in enhancing visible nail features but also in revealing cryptic features of diagnostic value and reducing the requirement for invasive procedures like nail biopsies, early diagnosis, directing management.